Pengembangan Kawasan Pariwisata Berkelanjutan Candi Borobudur sebagai Tema City Branding Kabupaten Magelang - Soesanta, Prabawa Eka; Putra, Imam Radianto Anwar Setia; Hutagalung, Oktavia Haryani (Research and Development Agency Ministry of Home Affairs, 2023)
The concept of city branding is needed to accelerate development in an area. Sustainable tourism development in Magelang Regency requires city branding by utilizing the existence of Borobudur Temple as a Super Priority Tourism Destination in Indonesia to become the main lever in efforts to improve the welfare of the local community. This study aims to analyze the importance of city branding in developing the Borobudur Temple tourism area as a world heritage site for Magelang Regency. This study used qualitative – descriptive was used to find, explain, and formulate conclusions using data collection techniques through interviews with key informants and FGDs with sources from the BOB, heads of cooperation, and leadership in charge of government affairs in the tourism sector. This research found the important benefits of establishing Borobudur Temple as a world heritage site and one of Indonesia's Super Priority Tourism Destinations to become a sustainable city branding for Magelang Regency to increase tourism promotion to domestic and foreign tourists. Establishing city branding in Magelang Regency requires collaboration and coordination between stakeholders, strategic area management, and micro, small, and medium enterprises empowerment. In conclusion, the implementation of sustainable development in Magelang Regency requires the establishment of city branding, which is linked to the existence of the development of the Borobudur Temple tourist area as a world heritage site.